Pengaruh Current Ratio, Net Profit Margin, Total Aset Turnover Terhadap Pertumbuhan Laba Perusahaan Beverages and Food Di Bursa Efek Indonesia - Eddy Purnairawan (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The background of this research is to measure the success of a company based on financial performance with the aim that readers can know about the extent of analysis of the influence of Current Ratio (CR), Net Profit Margin (NPM), Total Asset Turnover (TAT) variables on profit growth. Data was obtained using purposive sampling with the following criteria: (1) manufacturing companies listed on the Indonesia Stock Exchange (BEI) and consistently existed during the study period (2008 to 2012); (2) 6 similar manufacturing companies out of a total of 16 companies; (3) the company did not experience losses. The analysis results show that the data used in this study have met the requirements because there is no auto correlation. The regression analysis results show that the variables Current Ratio, NetProfit Margin, Total Asset either simultaneously or partially have a significant effect on profit growth. Therefore, the researcher would like to suggest that the company that the researcher studied and for other companies can increase profits every year and improve their financial performance.